Clinical vs. pathological staging in larynx tumors - Melo, Ana Sofia (2016)
Introduction: Larynx cancer represent about 30% of head and neck tumors, and 90% are squamous cell carcinomas. Discrepancies have been reported in clinical and pathological TNM staging in larynx cancer in several studies.Methods: Retrospective analysis of 179 patients undergoing laryngectomy between January 2009 and December 2014 in IPOFG of Coimbra. Results: With regard to the extent of the tumor (T), the restaging rate was 43.7%. The sensitivity in the detection of thyroid cartilage invasion or pre-epiglottic space was 55.6% and specificity of 83.4%. With regard to the cervical lymph nodes metastasis the re-staging rate was 36.7%. The sensitivity in the detection of cervical metastases was 85.1% and specificity of 78.5%.Conclusion: Similar to values from other consulted studies, we consider that the reclassification rate is high. The combination of CT data with those from MRI in cases of doubt may improve results. In cases of doubt we consider prudent to opt for surgical treatment so we have a more accurate staging. We emphasize the importance of follow-up taking into account the existence of significant false negatives.